2009
DOI: 10.1097/brs.0b013e3181b02988
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electrical Stimulation on Lumbar Spinal Fusion in Older Patients: A Randomized, Controlled, Multi-Center Trial

Abstract: The achievement of a good functional outcome was heavily dependent on the obtained walking distance. DC-stimulated patients tended to have better functional outcome as compared to controls. No negative effects of perioperative complications could be observed on the short-term functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The patient cohort in this study is taken from a multicenter randomized trial on the effect of direct current (DC) electrical stimulation in adjunct to uninstrumented spinal fusion [11, 12]. All patients underwent uninstrumented posterolateral spinal fusion using fresh frozen allograft and were braced postoperatively for 3-4 months.…”
Section: Methodsmentioning
confidence: 99%
“…The patient cohort in this study is taken from a multicenter randomized trial on the effect of direct current (DC) electrical stimulation in adjunct to uninstrumented spinal fusion [11, 12]. All patients underwent uninstrumented posterolateral spinal fusion using fresh frozen allograft and were braced postoperatively for 3-4 months.…”
Section: Methodsmentioning
confidence: 99%
“…Subgroup analyses investigating any differences in effect by type of stimulation, fusion level, and smoking status were preplanned. We were interested in exploring variations in effect between these population subgroups provided a higher rate of complications following spinal fusion are observed in patients who smoke or are elderly, which may influence the relative efficacy of electrical stimulation 15 . To explain any potential heterogeneity, we pre-specified a subgroup analysis of type of stimulation (pulsed electromagnetic fields, direct current electrical stimulation, and capacitive coupling).…”
Section: Assessment Of Risk Of Bias the Recommendations Outlined In mentioning
confidence: 99%
“…Mean follow-up was 14.1 (SD 5.1) months for radiographic outcomes. Three trials reported the use of pulsed electromagnetic fields (PEMFs) 13,20,21 , 1 trial used capacitive coupling (CC) 19 , and 2 trials used direct current (DC) 15,16,36 . Furthermore, 1 trial had two intervention groups, of which one underwent PEMF and the other underwent DC 36 ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations